PENGEMBANGAN E-BOOK TEMATIK BERBASIS PROJECT BASED QUR’AN MENGGUNAKAN APLIKASI FLIP PDF PROFESSIONAL: (Studi Pengembangan di SD Islam Baitunnur Blora) - Muhammad Farih; Siti Zahratu Nasikhah (Muróbbî: Jurnal Ilmu Pendidikan, 2022)
The outbreak of Covid 19 in 2020 until now, the high moral decadence and online learning can be an educational solution that is expected by the community and the government. This study aims to determine the results of the validation test of the effectiveness of the development of Project Based Qur'an-based Thematic E-Books using the Flip Pdf Professional Application at Baitunnur Islamic Elementary School Blora. In addressing the needs of education during the pandemic and education that is able to grow and realize the teachings of Islam contained in the Qur'an and Hadith in everyday life. This research and development uses R&D with a 4D model, namely define, design, develop, disseminate. Validation was carried out by 2 material experts, media experts, 3 practitioners to assess the product and 38 students for product effectiveness. Based on the results of the validation test results from material experts, the percentage results are 100% in the Very Good category, the results of the media expert test are 71.15% in the Good category, from 3 practitioners of class IV Al Jabbar it is 100%, class IV Al Farabi is 80%, Ar Razy is 82.5% with very good category. The resulting E-Book product is in accordance with the 2013 curriculum and is integrated with Qur'anic verses with various projects, to achieve educational goals and instill religious values in daily life if it meets the predicate good for media evaluation, very good for assessment of teaching materials, and tested with very good results.